Implementation of LEAD - Part I: Legislative Analysis and Regulations Development - Hunter Moorman (Educational Considerations, 1989)
Policy specifications set the directions and boundaries for program implementation and created a set of decision choices that ED had to make in the implementation process. (Development and Implementation of LEAD)